2015
DOI: 10.1111/tct.12320
|View full text |Cite
|
Sign up to set email alerts
|

Survey of medical students’ use of social media

Abstract: It is possible that educating medical students about the dangers of online social media, and how to use it appropriately, could be worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Subjective improvements in students' self-reported performance 56,60,63,123,124 and objective increases in assessment outcomes 33,35,38,40,69,82,125 were reported, including in two studies with controlled designs. 32,80 However, it is unclear whether the differences found in the latter two studies result from the use of SoMe or other confounding variables such as weekly assessment 32 or earlier exposure to educational material.…”
Section: Academic Performancementioning
confidence: 99%
“…Subjective improvements in students' self-reported performance 56,60,63,123,124 and objective increases in assessment outcomes 33,35,38,40,69,82,125 were reported, including in two studies with controlled designs. 32,80 However, it is unclear whether the differences found in the latter two studies result from the use of SoMe or other confounding variables such as weekly assessment 32 or earlier exposure to educational material.…”
Section: Academic Performancementioning
confidence: 99%
“…7 Also, Kang et al, found that social media was wide spread among medical students. 8 The most significant strong point of our study is the comprehensive assessment of prevalence and pattern of social media and related sociodemographic factors and the large numbers of students from theoretical and practical faculties were included.…”
Section: Discussionmentioning
confidence: 99%
“…W e read with interest the article by Kang et al in which UK medical students answered questions on social media use before and after having received the General Medical Council (GMC) social media guidelines. 1 The authors hypothesise that the fall in 'correct' responses may be explained by individual interpretation of the context of each question. We feel that this approach highlights students' diffi culties in applying guidelines to individual scenarios, because professionalism must be taught.…”
mentioning
confidence: 99%